The role of informal sector solid waste management practices to climate change abatement: A focus on harare and mutare, Zimbabwe: This work is partly presented at 8th World Climate Congress, May 10-11, 2019 Bangkok, Thailand - Jerie, Steven (Insight Medical Publishing, 2022)
The aim of this study was to examine the impact of waste management practices in the informal sector on climate change in Zimbabwe with particular reference to the cities of Harare and Mutare A multi-methods research design that triangulates quantitative and qualitative approaches was employed. A multi-methods research design that triangulates quantitative and qualitative approaches were employed. In Harare and Mutare, the city councils are experiencing major problems in collecting and minimizing the huge amounts of waste that could otherwise have negative impacts on local climate. Analysis of results gathered from the study, therefore, highlighted (a) the lack of recognition of the crucial role that could be played by the enterprises in reducing the amount of waste; and (b) the low rates of resource recovery and recycling in the enterprises which are vital waste minimization strategies as postulated in the principles of industrial ecology.